2018
DOI: 10.2754/avb201887030247
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and characterization of canine parvovirus-2 affecting canines of South Gujarat, India

Abstract: The present study was carried out in the region of South Gujarat, India, to determine the prevalence and predisposing factors of canine parvovirus-2 (CPV-2) infection in acute gastroenteritis of pups. Further, haemagglutination (HA) test, enzyme linked immunosorbent assay (ELISA), polymerase chain reaction (PCR) and rapid immunochromatography test were compared for diagnosis and prevalent CPV-2 types were ascertained. A total of 73 diarrhoea samples were collected and out of those 32, 33 and 35 were found posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The present study also reinforced the established fact that among pedigreed dogs, breeds such as Labrador retriever, German shepherd, and Pomeranian were most affected, while dogs below 3.5 months of age were at greater risk and males were having more percent positivity. With the sequence analysis of VP2 gene, the prevalence of CPV 2a has been commonly observed in many earlier studies [8,[11][12][13][14][15][16][17][18]. Similarly, a few studies have also indicated the presence of both CPV 2a and CPV 2b [8,11] in the samples from dogs.…”
Section: Discussionmentioning
confidence: 92%
“…The present study also reinforced the established fact that among pedigreed dogs, breeds such as Labrador retriever, German shepherd, and Pomeranian were most affected, while dogs below 3.5 months of age were at greater risk and males were having more percent positivity. With the sequence analysis of VP2 gene, the prevalence of CPV 2a has been commonly observed in many earlier studies [8,[11][12][13][14][15][16][17][18]. Similarly, a few studies have also indicated the presence of both CPV 2a and CPV 2b [8,11] in the samples from dogs.…”
Section: Discussionmentioning
confidence: 92%
“…The lower CCoV prevalence in our study concludes that CCoV does not prevail as CPV is, in south Gujarat, as there is no past reports from this region on prevalence of CCoV, whereas CPV is endemic in south Gujarat as reported by Mehta et al (2017), Pandya et al (2017) and Sharma et al (2018). LFA test is rapid, quick, simple, usable and comparatively inexpensive at the field level, which make it the first choice of clinical support at the field and veterinary dispensaries for diagnosis.…”
Section: Results a N D Discussionmentioning
confidence: 47%
“…2). Pandya et al (2017) reported 37.70 % prevalence of CPV, while Sharma et al (2018) reported 50 % prevalence of CPV by employing same LFA test. Agnihotri et al (2017) reported overall prevalence of 8 % and 50 % for CCoV and CPV, respectively, while Sakulwira et al (2003) reported 12.8 % and 62.8 % prevalence of CCoV and CPV-2 respectively by using molecular based detection technique.…”
Section: Results a N D Discussionmentioning
confidence: 86%
See 2 more Smart Citations